KURIKULUM PENDIDIKAN BERBASIS MULTIKULTURAL - Matsuroh Matsuroh (Millah: Journal of Religious Studies, 2010)
This article discusses the importance of design-based multicultural education curriculum. The diversity of social, cultural, political aspirations, and economic capacity is a difficult reality denied. Diversity is what should be the object of preparing the curriculum. With the approach of multicultural education curriculum is expected to Indonesia with the Kurikulum Berbasis Kompetensi (KBK) is able to accommodate the various realities of the diversity that exists.